2018
DOI: 10.1007/s40204-018-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic vs. synthetic granules for bone tissue engineering: an in vitro study

Abstract: The aim of this study was to compare human dental pulp stem cells’ (DPSCs) attachment, proliferation and osteogenic differentiation on allogenic and synthetic biphasic bone granules. In this in vitro study, two types of bone granules were used: allograft [freeze-dried bone allograft (FDBA)] and biphasic granules [hydroxyapatite/beta-tricalcium phosphate (HA/β-TCP)]. By isolation of DPSCs, their attachment to bone granules was observed by scanning electron microscope (SEM) at day 1 and 7 of cultivation. Vital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Hydroxyapatite (HA) and tricalcium phosphate (TCP) are categorized as bioceramic materials with excellent biological properties, among which their non-reactivity and osteoconductivity can be highlighted [ 1 ]. Their use as bone substitutes has been extended in several medical and dental specialties [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HA) and tricalcium phosphate (TCP) are categorized as bioceramic materials with excellent biological properties, among which their non-reactivity and osteoconductivity can be highlighted [ 1 ]. Their use as bone substitutes has been extended in several medical and dental specialties [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role played by the behavior of the DPSC in the regeneration of bone tissue is regulated by the secretion of paracrine factors and signaling, deposition of extracellular matrix, and cell-cell and cell-biomaterial interaction, considered key factors in tissue engineering (Table 1). Studies have shown the high potential of DPSC in the regeneration of bone tissue (13)(14)(15)(16)(17) and in regenerative cartilage treatments (18). It has been demonstrated that implantation of PDLSC and DPSC directly into the site of the defect may maintain their MSC characteristics after in-vivo implantation (19).…”
Section: Transplantation Of Mesenchymal Stem Cells and Storage Conditmentioning
confidence: 99%